DBS Improves FOG in Patients with PD - Rizzo, Toni (MD Conference Express, 2014)
High-frequency deep brain stimulation (DBS) is effective for relief of Parkinson’s disease (PD) symptoms. However, studies on the effect of subthalamic nucleus DBS (STN-DBS) on freezing of gait (FOG) have reported inconsistent results, with some suggesting that STN-DBS alleviates FOG [Davis JT et al. Clin Neurol Neurosurg 2006] and others reporting worsening of gait and balance [van Neunen BFL et al. Mov Disord 2008; Krack P et al. N Engl J Med 2003]. This article discusses the the Vercise Implantable Stimulator for Treating Parkinson’s Disease trial [VANTAGE; NCT01221948].